Collecting Distributed Knowledge For Community’s Smart Changes - Sciullo, Alessandro; Occelli, Sylvie (TeMA - Journal of Land Use, Mobility and Environment, 2013)
The paper deals with the role of ICT in innovating government’s and the whole process of “policy production process”. By enhancing the connections between various governmental and social organizations, ICT supported knowledge flow s and the associated Socio Technical System may be a vehicle to support innovation in the public sector. In fact, they would enable governments to better cope with the uncertainties of a complex environment. The MIDA Project carried out in the territory of Asti Province (Piedmont) can be considered as an attempt to engage in building such as a system. The Project uses a crowd sourcing approach and it involves citizens in collecting data concerning broadband coverage, Internet access and usages. From a research standpoint, MIDA represented an opportunity to test the role of Internet as a dynamic collaborative environment where statistically relevant data and interpreted information could be merged. In terms of policy, the project stood as an opportunity for the local government to engage itself in a new policy approach to grasp people’s needs and improve service delivery. <!–[if gte mso 9]> <![endif]–> The paper deals with the role of ICT in innovating government’s and the whole process of “policy production process”. By enhancing the connections between various governmental and social organizations, ICT supported knowledge flow s and the associated Socio Technical System may be a vehicle to support innovation in the public sector. In fact, they would enable governments to better cope with the uncertainties of a complex environment. The MIDA Project carried out in the territory of Asti Province (Piedmont) can be considered as an attempt to engage in building such as a system. The Project uses a crowd sourcing approach and it involves citizens in collecting data concerning broadband coverage, Internet access and usages. From a research standpoint, MIDA represented an opportunity to test the role of Internet as a dynamic collaborative environment where statistically relevant data and interpreted information could be merged. <span style="font-size: 10.0pt; line-height: 115%; font-family: ’Calibri’,’sans-serif’; mso-fareast-font-family: ’Times New Roman’; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: EN-US;" lang="EN-US">In terms of policy, the project stood as an opportunity for the local government to engage itself in a new policy approach to grasp people’s needs and improve service delivery.<!–[if gte mso 9]> Normal 0 14 false false false IT X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>